Depression and PTSD as Predictors of Attrition in Older Adult Exercise Programs: A Systematic Review. Issue 1 (January 2023) - Ha, Anh; Wilkins, Stacy Schantz; Melrose, Rebecca J.; Lee, Cathy C.
Abstract : Background: In older adults, exercise is extremely important and has been demonstrated to improve physical health, cognition, and mood. However, attrition in exercise programs in general is high, with up to 50% of participants leaving in the first 3 to 6 months. Methods: A systematic review of PubMed and PsycINFO databases was conducted using PRISMA criteria assessing the association of baseline depression and/or posttraumatic stress disorder (PTSD) with attrition rates in older adult exercise programs. Results: Ten articles were identified that assessed baseline depression and attrition in older adult exercise programs. No studies assessed baseline PTSD as a risk for attrition. Attrition rate overall ranged from 19% to 38%, and depression at baseline was found to be significantly associated with higher attrition rates. Other factors associated with attrition included anxiety, lower life satisfaction, worse cognitive health, higher illness rating, shorter program duration, common illnesses, lower social support, male sex, single relationship status, and transportation dependence. Discussion: Depression at baseline was significantly related with increased attrition in older adult exercise programs. Screening and consideration of adjunctive mood treatment are recommended. Further study of PTSD as an attrition risk is recommended, particularly in veteran or other populations with greater base rates.